Tuning of alpha-silyl carbocation reactivity into enone transposition: application to the synthesis of peribysin D, E-volkendousin, and E-guggulsterone - Athawale, Paresh R.; Zade, Vishal M.; Krishna, Gamidi Rama; Reddy, D. Srinivasa (Organic Letters, 2021)
A reliable method for enone transposition has been developed with the help of silyl group masking. Enantio-switching, substituent shuffling, and Z-selectivity are the highlights of the method. The developed method was applied for the first total synthesis of peribysin D along with its structural revision. Formal synthesis of E-guggulsterone and E-volkendousin was also claimed using a short sequence.